1 Löse nach dem Gleichsetzungsverfahren.

a) $y = 3x + 10 \\y = 2 - x$
b) $y = 3x + 10 \\ y = 2 - x$
c) $x = 3y - 5 \\ x = 2y - 9$
d) $y = 4x - 2 \\ y = 5x - 5$
e) $2y = 4x + 2 \\ 2y = 10x - 4$
f) $2 - x = 2y \\ x = 2y$
g) $3y = 4 - x \\ 3y = 9x - 3$
h) $y = 10 - 5x \\ 5 - 4x= y$

2 Löse nach dem Einsetzungsverfahren.

a) $x = y - 1 \\ y = 2x + 2$
b) $y = 3x + 10 \\ 2 = y + x$
c) $2x = 6y - 10 \\ 2y = 2x + 18$
d) $y = 4x - 2 \\ y = 5x - 5$
e) $2y = 4x + 2 \\ y = 5x - 2 $
f) $2 - x = 2y \\ x = 2y$
g) $4 - 3y = x \\ 3y = 9x - 3$
h) $y = 10 - 5x \\5 - y = 4x$

3 Löse nach einem Verfahren deiner Wahl.

a) $x = y - 1 \\ 3x + y = 5x + 2$
b) $y = 3x + 10 \\ - y = -2 + x$
c) $2x = 2(3y - 5) \\ y = x + 9$
d) $y = 4x - 2 \\ y = 5x - 5$
e) $-2y = - (4x - 2) \\ 2y = 2(5x - 2) $
f) $ 2 - 5x = 2y - 4x \\ x = 2y$
g) $4 - 3y = x \\ y = 3x - 1$
h) $-12x = -2 + 2y \\ 3x + 9 = 0$